Evaluation of protective immune responses induced by DNA vaccines encoding Echinococcus granulosus EgM123 protein in Beagle dogs - Wang, Ning; Xian, Jinwen; Zhao, Pengpeng; Zhao, Wenqing; Pu, Na; Jia, Xinyue; Zhang, Yanyan; Bo, Xinwen; Wang, Zhengrong (Frontiers in Veterinary Science, 2024)
IntroductionEchinococcus granulosus, known as cystic echinococcosis, is a prominent zoonotic parasitic disease of significant global concern. The definitive hosts serves as the primary reservoir for the transmission of echinococcosis, as well as a main factor in the prevention and control of the disease. Unfortunately, there is currently no commercially available vaccine for these hosts. Nevertheless, DNA vaccines show potential as a feasible strategy for the control and management of parasitic diseases.MethodsIn this study, the EgM123 antigen was selected for its well-documented immunogenic properties to develop a DNA vaccine aimed at combating E. granulosus infection in canines.ResultsThe results showed a marked increase in IgG levels in the group vaccinated with pVAX1-EgM123 DNA compared to the PBS group. Additionally, the cytokines IL-1, IFN-γ, IL-4, and IL-6 were significantly upregulated in the pVAX1-EgM123 DNA vaccine group. Furthermore, in comparison to the PBS control group, the EgM123 DNA vaccine group exhibited a notable 87.85% reduction in worm burden and a 65.00% inhibition in segment development.DiscussionThese findings indicate that the pVAX1-EgM123 DNA vaccine shows promising immunogenicity, successfully eliciting a targeted immune response in canines. Moreover, it significantly diminishes the worm burden and hinders the progression of tapeworms in the pVAX1-EgM123 DNA vaccine group. These findings suggest that the pVAX1-EgM123 DNA vaccine holds promise as a potential candidate vaccine for combating E. granulosus infection in dogs.